Exploring the practice of Iranian adolescent females during menstruation and related beliefs: a qualitative study - Mojgan Mirghafourvand; Abbas Ebadi; Shayesteh Jahanfar; Fatemeh Khorashadizadeh; Shayesteh Shirzadi (BMC, 2024)
Abstract Background Menstruation is a natural occurrence that women experience during their reproductive years and may encounter many years throughout their lifespan. Many adolescent females lack accurate knowledge about menstruation, so they may face issues from receiving incorrect information from unreliable sources. Our study aimed to investigate the practices and beliefs surrounding menstruation among Iranian adolescent females. Methods This qualitative study was conducted using conventional content analysis. A purposeful sampling method was used to select 18 adolescent females from secondary and high schools located in the three regions of Neyshabur City-Iran. Data were collected through in-depth, semi-structured interviews. Results Three main themes were extracted, consisting of lifestyle and related beliefs, lake of support, and awareness and information. Conclusions misconceptions and wrong behaviors during menstruation indicate that the lake of knowledge an traditional factors influence adolescent girls' health. The study provides the basis for intervention planning in this regard and different levels (individual, intrapersonal, health systems, and community).